The sustainability of China's silk trade: analysis of growth effect and the influencing factors - Feifei Lu; Minchen An; Qiao Liang (Frontiers in Sustainable Food Systems)
Silk and silk products have become one of the world's most vital traded commodities and China is the world's largest producer and exporter of silk products. This study uses statistical data on silk products trade of twenty-nine countries, who are main partners of China's silk trade. The data are mainly from the UN Comtrade database for the years 2002–2022. Utilizing the Constant Market Share (CMS) model, it analyzes the current status of China's silk product export trade. The study decomposes the factors influencing the export growth of silk products between China and other countries. The results indicate that from 2002 to 2022, China's export growth of silk products to other countries was mainly driven by increased export competitiveness. Specifically, silk and satin products and natural silk products have strong export competitiveness, while secondary silk products constrain export growth. In comparison, the dominant factor driving other countries' silk products export to China was the increasing demand in the Chinese market. Market fluctuations caused by the economic crisis and the epidemic have had an impact on the export value of natural silk products and silk and satin products, while secondary silk products, which have the highest value-added, have shown strong competitiveness.